2015
DOI: 10.1302/0301-620x.97b2.34331
|View full text |Cite
|
Sign up to set email alerts
|

Cemented versus cementless Oxford unicompartmental knee arthroplasty using radiostereometric analysis

Abstract: The most common reasons for revision of unicompartmental knee arthroplasty (UKA) are loosening and pain. Cementless components may reduce the revision rate. The aim of this study was to compare the fixation and clinical outcome of cementless and cemented Oxford UKAs. A total of 43 patients were randomised to receive either a cemented or a cementless Oxford UKA and were followed for two years with radiostereometric analysis (RSA), radiographs aligned with the bone-implant interfaces and clinical scores. The fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
93
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(103 citation statements)
references
References 26 publications
(19 reference statements)
9
93
0
1
Order By: Relevance
“…Patient selection and technique are under The Journal of Knee Surgery size for each subgroup precludes making any definitive conclusions but the results are consistent with several studies that found no difference in the revision rates for cemented and cementless Oxford UKAs in patients with lower BMIs. 8,[24][25][26] While the impact of hybrid fixation is not described in the literature, our findings suggest that hybrid Oxford UKAs may be safe for implantation in patients with morbid obesity. Further study on the influence of fixation type on the survival of Oxford UKA in patients with morbid obesity is warranted.…”
Section: Discussionmentioning
confidence: 59%
“…Patient selection and technique are under The Journal of Knee Surgery size for each subgroup precludes making any definitive conclusions but the results are consistent with several studies that found no difference in the revision rates for cemented and cementless Oxford UKAs in patients with lower BMIs. 8,[24][25][26] While the impact of hybrid fixation is not described in the literature, our findings suggest that hybrid Oxford UKAs may be safe for implantation in patients with morbid obesity. Further study on the influence of fixation type on the survival of Oxford UKA in patients with morbid obesity is warranted.…”
Section: Discussionmentioning
confidence: 59%
“…New Zealand Not cemented Oxford Phase 3 Jahromi 2004 [85] Australia No survival data Kaczmarczyk 2003[86] Poland No survival data Kendrick 2015 [87] UK No survival data Kubat 2011 [88] Czech…”
Section: Mmentioning
confidence: 99%
“…A reduction of RL within the first year seems to be typical in cementless fixation which can be observed in other studies of cementless OUKR. [8, 2022]. As explained by Hooper et al and Pandit et al, early radiolucencies might be ascribed to incompletely impacted implants which settle during weight-bearing.…”
Section: Discussionmentioning
confidence: 99%